Studi Literatur Dampak Perceraian Orangtua terhadap Hubungan Sosial dan Sikap Egois Anak di SMK Swasta Mandiri - Harahap, Ade Chita Putri; Yasri,, Ahmad; Mahyani, Alya; Syahputri, Eka; Aufa, Najia Barouatul; Br Siregar, Nova Susanti; Medy, Putri Aulia; Hidayati, Syari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate the impact of parental divorce on children's social relationships and selfish attitudes. Parental divorce is a complex event and can have long-term consequences for a child's development. In this study, we used a qualitative approach to collect data on children who have experienced parental divorce. The results of this study are expected to provide a better understanding of the social and psychological impact of parental divorce on children. Keywords: parental divorce, social relations, selfish attitude.